2018
DOI: 10.1097/md.0000000000013065
|View full text |Cite
|
Sign up to set email alerts
|

The biologic effect of hydrogen sulfide and its function in various diseases

Abstract: Introduction:Hydrogen sulfide (H2S), a colorless, water soluble, flammable gas with a characteristic smell of rotten eggs, has been known as a highly toxic gas for several years. However, much like carbon monoxide (CO) and nitric oxide (NO), the initial negative perception of H2S has developed with the discovery that H2S is generated enzymatically in animals under normal conditions. With the result of this discovery, much more work is needed to elucidate the biologic effects of H2S. In recent years, its cytopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 97 publications
1
57
1
3
Order By: Relevance
“…In this study, although NaHS reduced SBP, it did not reduce it to the control level. This could be because H 2 S exerts its antihypertensive effects partially via induction of the eNOS/NO pathway, which was blocked by l ‐NAME in this study …”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In this study, although NaHS reduced SBP, it did not reduce it to the control level. This could be because H 2 S exerts its antihypertensive effects partially via induction of the eNOS/NO pathway, which was blocked by l ‐NAME in this study …”
Section: Discussionsupporting
confidence: 65%
“…This could be because H 2 S exerts its antihypertensive effects partially via induction of the eNOS/NO pathway, which was blocked by l-NAME in this study. 9 Co-administration of H 2 S and l-NAME, in this study, increased serum levels of NO in comparison to those in the hypertensive group; however, its levels were still significantly lower than those of the control group and the H 2 S control group. In agreement with these findings, pregnant rats receiving both l-NAME and NaHS had higher serum NO levels than hypertensive pregnant rats; it was suggested that this was due to an NOS independent pathway.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Recent studies have indicated that H 2 S plays a variety of pathophysiological roles in cell proliferation, antioxidation, anti-inflammation, anti-apoptosis, and so on in multisystemic diseases [10]. In skin disorders, H 2 S has been proved to promote cell proliferation in the HaCaT cell line (spontaneously immortalized keratinocyte cell line, adult, male) [11].…”
Section: Introductionmentioning
confidence: 99%